Identifying emerging principles of digital constitutionalism in EU law and policy - Pereira, Miguel (UNIO – EU Law Journal, 2025)
In past work, we have reviewed some of the difficulties that the new technological landscape has given rise to, specifically as it concerns the provision of digital services. One of the avenues that academia has explored as a conceptual framework to address such difficulties is the theory of digital constitutionalism. The European Union (EU) and its institutions appear to have adopted such a digital constitutionalist stance in their policy response. In past work, we strived to identify and isolate the core values of digital constitutionalism: the limitation (or re-balancing) of powers, the rule of law and transparency. With these in mind, we now turn to EU law and policy governing the provision of digital services to assess the extent to which such values have been adopted by the EU institutions. We contend that they have assumed a prominent role in the definition of EU law and policy for the digital sphere, to the extent that we can now recognise them as principles of EU law. To this end, we have reviewed two major pieces of legislation in this area (the GDPR and the DSA), as well as sectoral legislation (the AVMSD and the TERREG) and instruments of soft-law (the European Declaration on Digital Rights), including co-regulatory initiatives (the 2022 Code of Practice on Disinformation). From our research, three overarching principles have been identified, whose content and definition merit further investigation and academic debate: the principle of user empowerment, the principle of due process and the principle of transparency.